Математичне моделювання розвитку пітингоподібних дефектів методом коміркових автоматів - Торська, Роксана Володимирівна (Національний університет "Львівська політехніка", 2017)
Дисертація присвячена підвищенню продуктивності процесу прогнозування швидкості пітингової корозії на поверхні металів та сплавів за рахунок розроблення нових математичних моделей та удосконалення методів симуляції росту пітингоподібних дефектів. Для досягнення поставленої мети запропоновано підхід на базі коміркових автоматів із використанням околу комірки фон Неймана ІІ-го порядку, що дало змогу знизити часові затрати та підвищити точність визначення глибини дефекту, особливо для пітингів неправильної форми. Розроблено математичну модель, що відображає перехід від активного розчинення металу на поверхні до стадії метастабільного росту пітинга з врахуванням імовірності його переходу у пасивний стан. З використанням розробленої математичної моделі, удосконалено метод задання локальних правил переходу для коміркового автомата, що враховує анодні реакції, процеси дифузії, пасивації, репасивації, які відбуваються при пітинговій корозії. Результати дослідження полягають у порівнянні даних, отриманих шляхом моделювання із реальними даними про динаміку розвитку точкових пошкоджень на поверхні зразків. Практично підтверджена доцільність застосування запропонованого методу симуляції для моделювання процесів кородування сталей у нейтральних середовищах. Точність відтворення фізики процесів на мікро-рівні забезпечується врахуванням електрохімічних факторів, що беруть участь у формуванні досліджуваних дефектів. Диссертация посвящена повышению производительности процесса прогнозирования скорости питтинговой коррозии на поверхности металлов и сплавов путём разработки новых математических моделей и усовершенствования методов симуляции роста питтингообразных дефектов. Для достижения поставленной цели предложено подход на базе клеточных автоматов с использованием окрестности ячейки фон Неймана II-го порядка, что дало возможность снизить временные затраты и повысить точность определения глубины дефекта, особенно для питтинга неправильной формы. Разработана математическая модель, отражающая переход от активного растворения металла на поверхности к стадии метастабильного роста питтинга с учетом вероятности его перехода в пассивное состояние. С использованием разработанной математической модели, усовершенствован метод задания локальных правил перехода для клеточного автомата, учитывающий анодные реакции, процессы диффузии, пассивации, репасивации, которые происходят при питтинговой коррозии. Результаты исследования заключаются в сравнении данных, полученных путем моделирования с реальными данными о динамике развития точечных повреждений на поверхности образцов. Практически подтверждена целесообразность применения предложенного метода симуляции для моделирования процессов корродирования сталей в нейтральных средах. Точность воспроизведения физики процессов на микро- уровне обеспечивается учетом электрохимических факторов, участвующих в формировании изучаемых дефектов. The thesis is dedicated to increasing the performance speed of the forecasting process pitting on the surface of metals and alloys by developing new mathematical models and simulation methods of improving growth pit similar defects. To achieve this goal prompted an approach based on cellular automata with a neighborhood cell von Neumann II-nd order, which made it possible to reduce time costs and improve the accuracy of determining the depth of the defect, especially for irregularly shaped pitting. The mathematical model that reflects the transition from the dissolution of the active metal on the surface of the stage of growth of the metastable pitting against the likelihood of its transition to the passive state. Using the developed mathematical models, improved method of specifying the local transition rules for a cellular automaton, taking into account the anodic reaction, diffusion processes, passivation, repassivation that occur by pitting corrosion. Results of the study was to compare the data obtained by simulation with real data about the dynamics of the point of damage to the sample surface. Almost confirmed the feasibility of the proposed method simulation to simulate the corrosion of steel processes in neutral environments. Fidelity to the micro-level processes is provided taking into account the physics of electrochemical factors involved in the formation of the studied defects. It is discovered that the simulated defects correspond (by their shapes and parameters) to the defects obtained by the method of rapid tests under the laboratory conditions. By using the proposed method of simulation, is possible to predict the formation of pit like defects of not only the open type but also of a partly closed type and get the surface topography of the bottom. This becomes possible because the nature of formation of these defects is explained by different thicknesses and strength characteristics of the oxide films formed on the surfaces and by the acidity of corrosive media. These and other factors can easily be taken into account within the proposed model. Hence, it is worth noting that the possibility of simulation of hidden pits is also quite promising. However, their investigation under the actual conditions is difficult due to the restriction imposed by the methods of microscopy and profilometry (contact and contactless). According to the obtained results, the character of the evolution of defects in the course of simulation strongly depends on the initial conditions and, hence, the shapes of simulated pits and the pH values on the surfaces of the cavities were different at the end of simulation.
Математическое моделирование развития питингообразных дефектов методом клеточных автоматов
Mathematical modelling of the evolution pit similar defects on the basis of a method using cellular automata
Keywords: метод коміркових автоматів; математичне моделювання; симуляція; пітингова корозія; пітингоподібний дефект; метод клеточных автоматов; математическое моделирование; симуляция; питтинговая коррозия; питтингообразный дефект; cellular automata method; mathematical modelling; simulation; pitting corrosion; pit similar defect